Machine Learning Analysis of the Impact of Increasing the Minimum Wage on Income Inequality in Spain from 2001 to 2021 - Lacasa-Cazcarra, Marcos (Recent Progress in Science and Engineering, 2025)
The main aim of this work is to analyze the impact of the National Minimum Wage (NMW) on wealth redistribution in Spain during the 2001-2021 period. This research addresses a fundamental question: Does increasing the minimum wage effectively reduce income inequality and contribute to a more equitable wealth distribution without negatively impacting overall economic growth and employment? Using a complete statistical census provided by the Spanish Tax Administration Agency, this study examines how the increase in the NMW—which rose from €505.7/month (2001) to €1,108.3/month (2021)—affected income inequality and other macroeconomic indicators. A distinctive feature of this research is the use of a complete national census database, not a sample or projection, which provides more accurate results and more efficient predictive models that reflect the studied population. Through various machine learning models, it is demonstrated that income inequality has been reduced by raising the minimum wage. Contrary to the predictions of previous economic analyses, the increase in the minimum wage has not led to inflation or increased unemployment. On the contrary, it has been consistent with increased net employment, contained prices, and increased corporate profit margins. The main conclusion is that the increase in the minimum wage during the analyzed period has contributed to an effective redistribution of wealth, simultaneously increasing the country’s prosperity, employment, and business profits under the analyzed conditions.
A groundbreaking study published today in Recent Progress in Science and Engineering demonstrates that increasing Spain's National Minimum Wage (NMW) between 2001-2021 led to significant positive economic outcomes, challenging conventional economic theories. The research by Marcos Lacasa-Cazcarra leverages an unprecedented dataset: a complete statistical census from the Spanish Tax Administration Agency tracking all Spanish employees over two decades. This comprehensive data shows that as Spain's minimum wage more than doubled from €505.7/month to €1,108.3/month, income inequality measurably decreased. Most striking is that contrary to traditional economic predictions, these minimum wage increases didn't trigger inflation or unemployment. Instead, the analysis reveals increased net employment, contained prices, and even improved corporate profit margins. Using advanced machine learning techniques and network analysis, the study identified a particularly positive shift in wage distribution, with the percentage of workers earning €20,000-€40,000 nearly tripling from 5.85% to 15.61% of the workforce between 2001-2021. These findings provide compelling evidence that well-calibrated minimum wage policies can serve as effective tools for reducing inequality while simultaneously fostering broader economic prosperity - a finding with significant implications for policymakers worldwide interested in sustainable approaches to addressing income disparities.
Keywords: machine learning; minimum wage